HUBUNGAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP EXPOSE TIME DAN KEAKTIFAN BELAJAR SISWA SEKOLAH DASAR: SYSTEMATIC LITERATURE REVIEW - Nurhaedah; Asti; Annisa Ramadhani, Nur; Dewi, Nurhalisa; Berlian; Hamsa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study systematically examines the relationship between the implementation of the Jigsaw cooperative learning model and the expose time (duration of implementation) and learning activeness of elementary school students. The method used is a Systematic Literature Review (SLR) with the PRISMA protocol. Data were collected from Google Scholar, DOAJ, SINTA, and ResearchGate databases, with a publication range of 2019–2026. Three main findings emerged. First, the Jigsaw model consistently improves the learning activeness and outcomes of elementary school students across various subjects with an average increase in activeness ranging from 8% to 55% and average cognitive score gains of 12–20 points. Second, expose time acts as a moderating factor: implementations shorter than five hours fail to produce optimal effects, while implementations longer than fifteen hours risk inducing boredom; thus, a range of 9–15 lesson hours appears to yield the most stable improvements. Third, the relationship between expose time and learning activeness is non-linear, resembling an inverted U-curve. This study recommends that elementary school teachers design Jigsaw implementations with measured duration, supported by training in the expert and co-teaching phases as well as integration of interactive media.